Sphenoid sinus pneumatization · Vidian canal · Anterior clinoid process · Pterygoid process · Multidetector computed tomography. - Djoric, Igor; Kablar, Djurdjina; Milic, Ivan; Milic, Marina; Stankovic, Lazar; Radojicic, Zoran; Starcevic, Ana (Medical Research, 2026)
Background: Multidetector computed tomography of the sphenoid sinus is the most accurate method for visualizing sinus pneumatization and all anatomical variations. Objective: To characterize the patterns of pneumatization of the sphenoid sinus and assess the association with variations in the bony structures of the sinus in relation to gender and age groups. Methods: Retrospective CT analysis of 127 patients (43 men and 84 women). Pneumatization patterns, skull base extensions, and Vidian canal types were classified. Results: Bilateral increased sphenoid sinus pneumatization shows a very strong age association (p = 0.001), with clustering in middle-aged (40–52) and elderly (≥ 66) groups. Right-sided preserved sphenoid sinus pneumatization shows a statistically significant association with gender (χ² = 3.90, p = 0.048), with a higher proportion of males than females. Bilateral pneumatization (BPP) showed a statistically significant association with age (p = 0.019); individuals with BPP were significantly younger. Sellar type predominated (67.7%), with frequent posterior and lateral extensions. The dorsal sphenoid sinus configuration is the only variant showing a statistically significant association with age (χ² = 8.17, p = 0.043). Complete sellar type shows a strong, consistent positive association with both anterior clinoid and pterygoid process pneumatization on all sides (p ≤ 0.015, often < 0.001). Type III Vidian canal occurred in 40%. Vidian canal Type I is strongly associated with pterygoid process pneumatization, especially bilaterally (p < 0.001 in all cases). Conclusions: The cohort exhibits a highly pneumatized, surgically relevant sphenoid sinus phenotype, primarily developmental rather than symptom-driven.